Mimesis of Media: Found Footage Cinema and the Horror of the Real. Issue 2 (1st November 2015) - Unknown
Abstract : This article examines the post-millennial popularity of the found footage movie, in particular its engagement with the representational codes of non-fiction media. Whilst the majority of critical writings on found footage identify the 11 September attacks on the World Trade Centre as a key visual referent, they too often dwell on the literal re-enactment of the event. This article instead suggests that thesefi lms evoke fear by mimicking the aesthetic and formal properties of both mainstream news coverage and amateur recording. As such they create both ontological and epistemological confusion as to the reality of the events depicted. Rather than merely replicating the imagery of terror/ism, these films achieve their terrifying effects by mimicking the audiences' media spectatorship of such crisis.